Estimation of Postmortem Interval Using the Radiological Techniques, Computed Tomography: A Pilot Study - Jiulin Wang; Jilong Zheng; Jiaxin Zhang; Shoutao Ni; Biao Zhang (Wolters Kluwer Medknow Publications, 2017)
Estimation of postmortem interval (PMI) has been an important and difficult subject in the forensic study. It is a primary task of forensic work, and it can help guide the work in field investigation. With the development of computed tomography (CT) technology, CT imaging techniques are now being more frequently applied to the field of forensic medicine. This study used CT imaging techniques to observe area changes in different tissues and organs of rabbits after death and the changing pattern of the average CT values in the organs. The study analyzed the relationship between the CT values of different organs and PMI with the imaging software Max Viewer and obtained multiparameter nonlinear regression equation of the different organs, and the study provided an objective and accurate method and reference information for the estimation of PMI in the forensic medicine. In forensic science, PMI refers to the time interval between the discovery or inspection of corpse and the time of death. CT, magnetic resonance imaging, and other imaging techniques have become important means of clinical examinations over the years. Although some scholars in our country have used modern radiological techniques in various fields of forensic science, such as estimation of injury time, personal identification of bodies, analysis of the cause of death, determination of the causes of injury, and identification of the foreign substances of bodies, there are only a few studies on the estimation of time of death. We detected the process of subtle changes in adult rabbits after death, the shape and size of tissues and organs, and the relationship between adjacent organs in three-dimensional space in an effort to develop new method for the estimation of PMI. The bodies of the dead rabbits were stored at 20°C room temperature, sealed condition, and prevented exposure to flesh flies. The dead rabbits were randomly divided into comparison group and experimental group. The whole-body CT scans were performed on the experimental group of rabbits at different PMIs. NeuViz dual-slice spiral CT scanner (made by Neusoft Medical in China, 2 mm × 10 mm high-speed rare earth ceramic detector) is a 360° scan that could obtain two images, capable of providing a wide range of high-speed continuous spiral scan. Max Viewer (Version: 1.0.0131, Neusoft, Shenyang, China) is a CT image viewing software developed by Neusoft Medical. The software can be used to view and process images in various common methods and to measure a number of parameters, such as length, area, angle, and CT values. Statistical analysis was performed using SPSS1 Statistics 19.0 (SPSS, Inc., Chicago, IL, USA). A P ≤ 0.05 was considered statistically significant. We obtained the binomial regression equation of the CT values and the related coefficient (R2). In the future, we suggests that comprehensive analyses of various indicators of different organs could establish a diversified pattern to remedy the deficiencies and make the study of PMI estimation more scientific and enhance the operability.